(untitled) (Bulletin KNOB, 1989)
Excavations in Yemen have pointed out that more than 2000 years ago Yemen houses resembled present-day Sana’a dwellings. At Shabwa French archeologists discovered multi-floors, high palaces and dwellings consisting of more than 8 layers from the 3d century before Christ. Azal or Uzal is the old name for Sana’a and is mentioned in the book Genesis of the Old Testament. Of course one cannot determine whether Uzal really has founded the town Sana’a. On the other hand Sana’a is one of Arabia’s oldest towns. Until now no archeological research has been executed within the walls of the town. Sana’a always was a trade centre and till the year of the revolution (1962) three quarter of Sana’a’s active population has been employed at the market. To the south of Mecca a chain of mountains runs parallel with the Red Sea. The mountains reach heights of more than 300 meters, take care of a mild climate and collect the monsoon rains. Already in antiquity 80% of the Arabian peninsula population lived here. Near the Indian Ocean in the wadi’s the growth places of incense and myrrh are situated. The rich obtained great prosperity by the monopoly on the production and sale of these products from India to the Mediterranean. Little is known about the pre-Islamic period. Many columns and capitals have been applied tot the large mosque (800 AD). On the spot where according to the legend Christ has bidden during a visit to Sana’a a cathedral has been built, which is described as the largest Christian building to the south of the Mediterranean. The cathedral and the large royal palace Ghumdan both are disappeared, The Islamic period in Yemen starts in 656 AD (35). Ali ibn Ali Tarib, Mohammed’s son-in-law, stayed in a house in the south of Sana’a. As mentioned above, little is known about the development of the town in the pre-Islamic period. In the 3rd century AD the town must have had a large surface. The palace Ghumdan had 10 floors. This palace has been destroyed by order of the prophet or later by the caliphs. The large mosque has been built in the garden of the Ghumdan palace by order of the prophet. Descriptions by Ibn Rustah (900 AD) indicate that the houses at that time very much resembled modern dwellings. High houses raised in natural stones and bricks, adorned with plaster ornaments. He also describes the town when she was totally surrounded by walls. A description from 902 points out that there were 700 shops, 106 mosques, 12 bathing houses etc. After the conquest by the Turks the town pauperizes. A new flourishing period started after the first Turkish occupation in 1630. Anarchy and plundering almost totally destroyed Sana’a at the beginning of the 19th century. Further decay has been caused by the new Turkish conquest in 1872. In 1874 only 20.000 people still lived in Sana’a. After the departure of the Turks a period of rebuilding began and the population rose to ca. 50.000. During the revolution (1962) and the civil war again destructions take place. Modernization with the help of the Egyptians brought the town the largest damage after the revolution. Town-walls and gates have been pulled down and the large Al Tharir square was laid out. Nowadays ca. 350.000 people living there the town has grown enormously since the beginning of the seventies. The middle ages in Yemen lasted till 1962 and modernization passes more stormy than elsewhere in the world. The old town threatens to become victim of this development. For thousands of years Sana’a knew to preserve her unique character. How can this world monument (Unesco statement) be saved? In the following chapters a start will be sketched.